2011
DOI: 10.1111/j.1432-2277.2011.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast for bronchiolitis obliterans syndrome after lung transplantation: a pilot study

Abstract: Summary Bronchiolitis obliterans syndrome (BOS) remains the major hurdle to improve long‐term survival after lung transplantation, as its treatment remains troublesome. In this pilot study, we investigated the effect of montelukast (a leukotriene receptor antagonist) on the FEV1 decline after diagnosis of BOS and compared this with a control group. In both groups, 11 patients were included with BOS stage <3 and bronchoalveolar lavage (BAL) neutrophilia <15%, already being treated or concurrently being started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 25 publications
(48 reference statements)
2
52
0
Order By: Relevance
“…One study has reported that the 5-year survival rate is only 29 % among patients with both chronic GVHD and BOS [8]. Moreover, stabilization of lung function in BOS patients with HCT may be achieved by high-dose pulse corticosteroids [2], leukotriene receptor antagonists [9], and combinations of inhaled bronchodilators and glucocorticoids [10], whereas the efficacy of these drugs, except for leukotriene receptor antagonists, in BOS after lung transplant is unclear [20,21]. In addition, the diagnostic criteria for BOS after HCT and lung transplantation are slightly different [3,13,22].…”
Section: Discussionmentioning
confidence: 97%
“…One study has reported that the 5-year survival rate is only 29 % among patients with both chronic GVHD and BOS [8]. Moreover, stabilization of lung function in BOS patients with HCT may be achieved by high-dose pulse corticosteroids [2], leukotriene receptor antagonists [9], and combinations of inhaled bronchodilators and glucocorticoids [10], whereas the efficacy of these drugs, except for leukotriene receptor antagonists, in BOS after lung transplant is unclear [20,21]. In addition, the diagnostic criteria for BOS after HCT and lung transplantation are slightly different [3,13,22].…”
Section: Discussionmentioning
confidence: 97%
“…However, this beneficial effect seems to occur predominantly in patients with lymphocytic bronchiolitis, but not in those with bronchiolitis obliterans, and thus indicates that only in conditions with considerable inflammatory cell infiltrate can the progression of disease be delayed, whereas with only scant inflammation but pronounced fibrosis the potential benefit might be limited. Importantly, neutrophilia of .15% in the BAL fluid has been demonstrated to be predictive of FEV1 response to azithromycin in patients with BOS after lung transplantation [58], whereas patients without neutrophilia in the BAL benefited from the addition of the leukotriene receptor antagonist montelukast [59]. Transferring these findings to our study group, one would add azithromycin to the immunosuppressive regimen in those patients with histological lymphocytic bronchiolitis and relevant BAL neutrophilia, and additional montelukast for those patients with low neutrophilic lymphocytic bronchiolitis.…”
Section: Figurementioning
confidence: 87%
“…In the control group (n = 11), there was no significant change in the rate of FEV 1 decline (from 103 ± 20 ml/month before BOS diagnosis to 114 ± 27 ml/ month). Although it was concluded from this study that adding montelukast may be a promising treatment option in patients with low neutrophilic (< 15%) BOS and already or concurrently being treated with azithromycin, this data certainly need confirmation in a prospective placebo-controlled trial [14].…”
Section: Nonimmunosuppressive Agentsmentioning
confidence: 97%